The Relationship between House Environmental Condition and Mosquito Larvae Density (Diptera: Culicidae) in Medan Denai Sub-District, Medan City - Merina Panggabean; Yoan Carolina Panggabean; Lambok Siahaan; Adelina Haryani Sinambela; Irma Sepala Sari Siregar (Postgraduate, University of Mataram, 2025)
Mosquitoes are the primary vectors for disease transmission in tropical regions such as Indonesia, which has high humidity levels that support their reproduction. Household environmental conditions play a crucial role in determining the presence and density of mosquito larvae as disease vectors. The Medan Denai subdistrict is a densely populated area experiencing an increase in Dengue Hemorrhagic Fever (DHF) cases. This study analyzes the relationship between household environmental conditions and mosquito larvae density. A survey was conducted on 300 homes divided into three groups. Environmental condition data were collected through direct observation, while the presence of larvae was analyzed using the House Index (HI), Container Index (CI), and Breteau Index (BI) to calculate the Density Figure (DF). Results showed that 24% of homes tested positive for larvae, primarily in dispenser containers. A total of 61% of homes had unclean environmental conditions. The highest DF of 5.3 was found in the 1–100 home group, which falls under the high-risk category for disease transmission. Chi-Square analysis revealed a significant association between environmental conditions and larval density (p = 0.045). These findings underscore the importance of improving environmental conditions as a strategy for mosquito vector control.